A novel biomass gasification based cascaded hydrogen and ammonia synthesis system using Stoichiometric and Gibbs reactors. (February 2021) - Ishaq, H.; Dincer, I.
Abstract: This paper focuses on a new configuration of biomass gasification based cascaded ammonia synthesis and proposes two different configurations of ammonia synthesis system using the Stoichiometric and Gibbs reactors in the Aspen Plus V11. A new heat recovery technique from biomass gasification using syngas cooling is also proposed in this study. The proposed configuration comprises of a biomass gasifier, a heat recovery unit for syngas cooling, a combined cycle, water gas shift reactor system (WGSRS), pressure swing adsorption (PSA) and ammonia production unit. The ammonia based carbon-capturing system is incorporated to ultimately capture the CO2 emissions. The sensitivity analyses are conducted on each significant subsystem employed in the proposed configuration. The results obtained from the Gibbs reactors show that pressure has a positive effect while very high-temperature effects negative on the ammonia synthesis. The results also reveal that the cascaded ammonia synthesis offers high ammonia conversion rates. The designed system produces 21.9 kmol/h of ammonia and 3405 kW electrical power. The results obtained from the present sensitivity analysis are further presented and discussed. Highlights: New configuration of biomass gasification based cascaded NH3 synthesis is proposed. New heat recovery technique is proposed using the syngas cooling. The designed system produces 21.9 kmol/h of ammonia and 3405 kW electrical power. Overall exergy and energy efficiencies are found to 44.2% and 42.4% respectively.